2023
DOI: 10.3390/biom13101530
|View full text |Cite
|
Sign up to set email alerts
|

GlycA: Evaluation of a New Biomarker of Acute Pancreatitis

Ishani Shah,
William Yakah,
Awais Ahmed
et al.

Abstract: Background: Acute pancreatitis (AP) is a leading cause of gastrointestinal hospital admissions, with up to 40% mortality in patients with moderate–severe AP. Glycoprotein acetylation (GlycA) is measured as a nuclear magnetic resonance signal (NMR) of the post-translational modification of glycosylated acute-phase proteins released during inflammation. We aimed to investigate the role of GlycA as an inflammatory biomarker of AP. Methods: We prospectively enrolled 20 AP patients and 22 healthy controls and colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…Furthermore, GlycA was most elevated in MSAP with a slight increase in the SAP patients, suggesting increased inflammation levels in MSAP compared to MAP and SAP. Although the differences in GlycA between the groups in this study were not significantly different, it is notable that in a recent study, Shah and colleagues show that GlycA could be used as a novel diagnostic marker of inflammation in AP when compared to healthy controls (Shah et al, 2023).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, GlycA was most elevated in MSAP with a slight increase in the SAP patients, suggesting increased inflammation levels in MSAP compared to MAP and SAP. Although the differences in GlycA between the groups in this study were not significantly different, it is notable that in a recent study, Shah and colleagues show that GlycA could be used as a novel diagnostic marker of inflammation in AP when compared to healthy controls (Shah et al, 2023).…”
Section: Discussioncontrasting
confidence: 69%
“…Several NMR studies have shown that the integration of metabolites with meta-analysis of the transcriptome revealed a pancreatitis background in pancreatic cancer, congruent with AP being a risk factor to pancreatic cancer (Ketavarapu et al, 2022). Furthermore, 1 H-NMR metabolomics has been used to distinguish between AP patients and healthy controls or those presenting with abdominal pain (Lusczek et al, 2013; Villaseñor et al, 2014; Shah et al, 2023). In the study by Villaseñor and colleagues in 2014, the authors found changes in the lipid profile with high levels of low-density lipoprotein and unsaturated lipids, which are consistent with known disruptions in lipid metabolism in AP.…”
Section: Introductionmentioning
confidence: 99%